2011
DOI: 10.1111/j.1468-3083.2011.04012.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Tie2 levels: clinical association with microangiopathies in patients with systemic sclerosis

Abstract: Soluble Tie2 domain (sTie2) may be related to the development of vascular abnormalities in SSc, possibly by modulating the Ang/Tie2-mediated angiogenic process. Furthermore, the serum sTie2 levels may serve as a useful marker for SSc-related PAH, contributing to early diagnosis and therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…However, apart from discrepancies that might arise from studying such a heterogeneous disease, these differences might also be attributed to the use of plasma [32] instead of serum. Similar to our observations, the serum levels of sTie2 were found to be elevated by Noda et al [17] and Dunne et al [32], however, the latter study only demonstrating significant differences in the lcSSc subgroup. The study by Gerlicz et al showed a trend towards higher levels of sTie2 in both SSc subsets compared with healthy controls, yet the data were not statistically significant [33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, apart from discrepancies that might arise from studying such a heterogeneous disease, these differences might also be attributed to the use of plasma [32] instead of serum. Similar to our observations, the serum levels of sTie2 were found to be elevated by Noda et al [17] and Dunne et al [32], however, the latter study only demonstrating significant differences in the lcSSc subgroup. The study by Gerlicz et al showed a trend towards higher levels of sTie2 in both SSc subsets compared with healthy controls, yet the data were not statistically significant [33].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to mbTie2, little is known about soluble Tie2 (sTie2), the extracellular domain of the Tie2 receptor, which is released by proteolytic cleavage by matrix metalloproteases upon stimulation with VEGF in a process also referred to as shedding [13, 14]. sTie2 is detectable in healthy individuals, and increased serum concentrations were measured in cardiovascular diseases, diabetic retinopathy [15], and SSc [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…In the replication cohort, sera was also taken at rest from the forearm, in the morning, and stored locally before shipment to our laboratory, in the days after the patient meeting. Serum levels of eight endothelial factors that have been shown to be implicated in SSc (VEGF, placenta growth factor (PlGF), sVCAM, angiopoietin-2, endoglin, endostatin, endothelin-1 and Tie-2) were measured by using the quantitative sandwich enzyme-linked immunosorbent assay (ELISA) technique (Quantikine kits; R&D systems) [11-14,17,18,26-28]. No patient in our cohort had regular alcohol consumption, which has been reported to have an important influence on serum levels of VEGF.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, increased Ang-2 strongly correlated with skin and lung involvement as well as with disease activity and digital ulcers. In 2011, Noda et al [18] reported no significant difference of Tie-2 levels in both SSc patients and healthy controls. However, in their study, after adjustment of the cut-off value based on the data of normal controls, 27% of SSc patients did show elevated serum Tie-2 levels and Tie-2 correlated with pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%